2021
DOI: 10.1038/s41598-021-99711-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic control of neurite outgrowth direction

Abstract: This study investigated a method to control neurite outgrowth direction using ultrasound vibration. An ultrasound cell culture dish comprising a glass-bottom culture surface and a glass disc with an ultrasound transducer was fabricated, and undifferentiated neuron-like PC12 cells were grown on the dish as an adherent culture. The 78 kHz resonant concentric flexural vibration mode of the dish was used to quantitatively evaluate the neurite outgrowth direction and length. Time-lapse imaging of cells was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…These studies also found that LIPUS activates the NGF-induced ERK1/2-CREB-Trx-1 pathway through stretch-activated ion channels to promote neurite outgrowth. In addition, Maruyama et al demonstrated that ultrasound stimulation under certain conditions increased NGF-induced neurite lengths and controlled the direction of neurite outgrowth [29]. Hoop et al reported the interesting observation that ultrasound stimulation leads to neurite outgrowth, but with piezoelectric stimulation using the piezoelectric polymer polyvinylidene fluoride (PVDF) instead of NGF [30].…”
Section: Ultrasound Stimulationmentioning
confidence: 99%
“…These studies also found that LIPUS activates the NGF-induced ERK1/2-CREB-Trx-1 pathway through stretch-activated ion channels to promote neurite outgrowth. In addition, Maruyama et al demonstrated that ultrasound stimulation under certain conditions increased NGF-induced neurite lengths and controlled the direction of neurite outgrowth [29]. Hoop et al reported the interesting observation that ultrasound stimulation leads to neurite outgrowth, but with piezoelectric stimulation using the piezoelectric polymer polyvinylidene fluoride (PVDF) instead of NGF [30].…”
Section: Ultrasound Stimulationmentioning
confidence: 99%
“…Our ES profiles could not trigger directional growth. Other approaches include light [101], fibrous scaffolds [95], ultrasound [102], or biochemical gradients [103], but they are limited by the complex and rather inaccessible structure of the cochlea. Our CI-like ES patterns could not boost or guide neurite outgrowth but decreased the number and length of neurites.…”
Section: Conclusion and Implications For Cochlear Implantationmentioning
confidence: 99%
“…It also controls the directionality of the growing tip of the neurite and promotes neuronal differentiation. 54 The interaction of myosin and actin is required for axon retraction. To achieve this, myosin II becomes activated and intra-axonal F-actin bundles are formed, resulting in the generation of a force driven by myosin II.…”
Section: ■ Microtubule Modulating Agentsmentioning
confidence: 99%
“…A study recently reported that ultrasonication significantly increases the length of neurites compared to those of unsonicated cells in a culture dish. It also controls the directionality of the growing tip of the neurite and promotes neuronal differentiation . The interaction of myosin and actin is required for axon retraction.…”
Section: Growth Cones and Retraction Bulbsmentioning
confidence: 99%